2019
DOI: 10.1038/s41431-019-0369-6
|View full text |Cite
|
Sign up to set email alerts
|

A pathway-driven predictive model of tramadol pharmacogenetics

Abstract: Predicting metabolizer phenotype (MP) is typically performed using data from a single gene. Cytochrome p450 family 2 subfamily D polypeptide 6 (CYP2D6) is considered the primary gene for predicting MP in reference to approximately 30% of marketed drugs and endogenous toxins. CYP2D6 predictions have proven clinically effective but also have welldocumented inaccuracies due to relatively high genotype-phenotype discordance in certain populations. Herein, a pathwaydriven predictive model employs genetic data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…These results point towards a higher relevance of combined CYP2D6*4,*10 and MC4R variations as well as a correlation of CYP2D6*41 with UGT2B7 variations. This is in line with previous data showing a general combined co-occurence of CYP2D6 / UGT2B7 variability [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results point towards a higher relevance of combined CYP2D6*4,*10 and MC4R variations as well as a correlation of CYP2D6*41 with UGT2B7 variations. This is in line with previous data showing a general combined co-occurence of CYP2D6 / UGT2B7 variability [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…These studies concluded that CYP2D6 genotyping may be important in identifying the cause of unexpectedly high or low tramadol-metabolite ratios in post-mortem blood samples [ 19 , 27 ]. Furthermore, one study looked at 16 variants from five genes involved in tramadol pharmacokinetics and pharmacodynamics and concluded that a set of 16 loci from these five genes can predict tramadol/metabolite ratio with over 90% accuracy, which is greater than using CYP2D6 alone [ 30 ]. Similarly, the oxycodone-to-oxymorphone concentration ratio showed a significant correlation with CYP2D6 activity when death was unrelated to intoxication and CYP2D6 PMs and IMs had significantly higher oxycodone concentrations compared to EMs and UMs [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Blue rectangles and horizontal lines represent CYP2D6 exons and introns, respectively; single nucleotide polymorphism (SNP) rs numbers are provided for select * allele defining loci; designated SNP alleles are relative to the hg19 reference genome. CYP2D6*1A is the wild type * allele; CYP2D6*7 and CYP2D6*10A demonstrate how a single SNP, or a collection of SNPs along the length of the gene, confer different * alleles investigating genetic variability of trans-acting metabolic proteins, in particular those implicated in pain propagation/relief, opiate metabolism, and addiction (Altar, Carhart, Allen, Hall-Flavin, Dechairo, et al, 2015a;Altar, Carhart, Allen, Hall-Flavin, Winner, et al, 2015b;Crist & Berrettini, 2014;Fujita et al, 2010;Rahikainen et al, 2018;Rakvag et al, 2005;Wendt, Novroski, Rahikainen, Sajantila, & Budowle, 2019). These additional genes of interest include several members of the ABC and OPR families.…”
Section: Box 1 Molecular Autopsy and Sudden Unexpected Death In The Ymentioning
confidence: 99%
“…Altar et al demonstrated that combinatorial approaches to predicting MP have significantly more efficacious patient outcomes when compared to a single-gene single-phenotype model for psychiatric compounds (Altar, Carhart, Allen, Hall-Flavin, Dechairo, et al, 2015a;Altar, Carhart, Allen, Hall-Flavin, Winner, et al, 2015b). Pathway-driven pharmacogenetic studies have been performed in relatively few drug classes and typically utilize relatively few loci (i.e., genes or SNPs; Altar, Carhart, Allen, Hall-Flavin, Winner, et al, 2015a;Baber et al, 2015;Bastami et al, 2014;Sistonen et al, 2012;Wendt et al, 2019). The success of these models is still relatively low but the community is dedicating substantial resources to developing extended ADME-R predictive models using common and rare variants, copy-number variation, and various computational algorithms for performing the predictions (see also Jamei et al, 2009;Jornil et al, 2013 for existing workflows/software).…”
Section: Rare Variants and Pathway-driven Prediction Of Drug Responsementioning
confidence: 99%
See 1 more Smart Citation